2019
DOI: 10.3126/tujm.v6i0.26589
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antibacterial Activity of Juice and Peel Extract of Citrus Fruits

Abstract: ABSRTACTObjectives: This study was aimed to compare the antibacterial activity of peel and juice extracts of citrus fruits.Methods: The antibacterial activity of juice and peel extract of fi ve selected citrus fruits [C1-Citrus reticulata (mandarin orange), C2-Citrus limetta (sweet lime), C3-Citrus aurantifolia (lime), C4-Citrus limon (lemon) and C5-Citrus maxima (pommelo)] on three Gram positive and fi ve Gram negative bacterial strains were examined. The juice and peel extract of citrus fruits was obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
5
9
0
Order By: Relevance
“…In alignment with our study, Kadhim Hindi and Ghani Chabuck (2013) revealed that lemon juice showed the high inhibition zone of (28 mm) against Enterococcus faecalis bacterial strain (Kadhim Hindi and Ghani Chabuck, 2013). Also, a similar finding was shown by Alisha Shakya et al (2019) who reported an inhibition zone of 20.66 mm against Pseudomonas aeruginosa in lemon samples (Shakya et al, 2019). Additionally, our finding revealed that grampositive bacterial strains exerted better inhibition zone than gram negative in both farming systems.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In alignment with our study, Kadhim Hindi and Ghani Chabuck (2013) revealed that lemon juice showed the high inhibition zone of (28 mm) against Enterococcus faecalis bacterial strain (Kadhim Hindi and Ghani Chabuck, 2013). Also, a similar finding was shown by Alisha Shakya et al (2019) who reported an inhibition zone of 20.66 mm against Pseudomonas aeruginosa in lemon samples (Shakya et al, 2019). Additionally, our finding revealed that grampositive bacterial strains exerted better inhibition zone than gram negative in both farming systems.…”
Section: Discussionsupporting
confidence: 90%
“…The reason behind this is that gram-negative bacteria possess extra outer membrane, which might be able to behave as a barrier for the passage of this polyphenolic compounds. Similarly, other study showed resistance of gram negative against lemon peels due to such alterations in structures between gram positive and gram negative (Shakya et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the present study, C. reticulata peel extract revealed good antibacterial activity against various pathogenic bacteria, similar to that noticed in a number of studies [51,52] which seemed to have beneficial effects on wound healing.…”
Section: Antimicrobial Activitysupporting
confidence: 91%
“…The essential oil was isolated from the peels (Edogbanya et al 2019) and also found in its leaves (Al-Aamri et al 2018;Lemes et al 2018). The peels are also effective against E. coli (Shakya et al 2019). The peel extract which can inhibit the growth of S. aureus in the sensitive category is 80% (Ekawati et al 2019).…”
Section: Discussionmentioning
confidence: 99%